INTERPRETATION OF NATURE AND HUMAN RELATIONS IN MODERN UZBEK STORYTELLING - Shukurova Bahor Boltayevna (American Journals, 2023)
The fact that man has always lived in harmony with nature since creation determines the relevance of general research related to this topic. There has always been an intimate connection between man and nature. Therefore, this topic is interpreted as one of the main issues in the literature. Done. Sh. Kholmirzayev's and N. Eshonkul's artistic skills in storytelling are explored through their stories reflecting nature and human relations.
Keywords: Shukur Kholmirzayev, Boysun, Surkhan Eli, Uzbek, nature and man, story,